Riparian Zones—From Policy Neglected to Policy Integrated - Urbanič, Gorazd; Politti, Emilio; Rodríguez-González, Patricia María; Payne, Robin; Schook, Derek; Alves, Maria Helena; Anđelković, Ana; Bruno, Daniel; Chilikova-Lubomirova, Mila; Di Lonardo, Sara; Egozi, Roey; Garófano-Gómez, Virginia; et al. (Frontiers in Environmental Science, 2022)
1. Riparian zones are vital areas of interaction between land and rivers and are often degraded by several pressures such as urbanisation, intensive agriculture and river engineering works. 2. This policy brief provides five key policy messages and recommendations to be considered by policy-makers, scientists, managers, and stakeholders to enhance riparian zone management. 3. Adopting an integrated socio-economic and environmentally dynamic view will ensure the sustainable management of riparian zones. 4. In light of climate change, it is critically important to conserve and/or restore the ecological integrity of riparian zones. 5. European Union Directives and national-scale legislation and regulations need updating to ensure coordinated implementation of riparian zone-related policies. 6. Stakeholder knowledge exchange, policy co-creation and adaptive management are key to enhancing riparian zone functions.